SEISMIC HAZARD FUNCTION (SHF) INVESTIGATION FROM THE 10 OCTOBER 2018 SITUBONDO EARTHQUAKE FAULT FOR SITUBONDO AND ITS SURROUNDING CITIES - Hajah Patimah, Sindi
The 10 Oct 2018 Situbondo earthquake occurred around the populous cities. The characterization of the fault that generated the 2018 Situbondo earthquake has been carried out in previous studies. In this study, a further study was carried out by adding three observation stations to determine the seismic hazard caused by this fault source through a seismic hazard function (SHF) study using the Probabilistic Seismic Hazard Analysis (PSHA) method. Estimation of slip rate empirically obtained 0.6 mm/year. In addition, by applying the checkerboard test, the rupture zone area is 15 km x 25 km. PGA was estimated using Ground Motion Prediction Equations (GMPEs) calculated on the bedrock and obtained seismic hazard curves for the observed cities. This curve is described with the plot of PE as a function of PGA. The result shows that source is potencially for the cities of Situbondo, Sumenep, Probolinggo, Jember, Surabaya and Sidoarjo. These are indicated by relatively high curve values. In addition, based on the results of PDF calculations, it is found that the probability of the source generating an earthquake with > Mw 6.2 is less than 0.5%.